PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE HOLLYWOOD SQUARES REVIEW UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN HIDROKARBON DAN MINYAK BUMI DI KELAS XI SMAN 2 PEKANBARU - Astuti, Sri Puji; Amran, Elva Yasmi; ', Rasmiwetti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Theresearchwas conducted become of the low learning achievement of student on the subject of hidrocarbon and petroleum who was not reached the minimum completeness criteria (KKM) was 75 that have been esthabilished in school. The research aims to improve learning achievement of student on the subject of hidrocarbon and petroleum.The samples is class XI MIA 4. The research is a kind of experiment research with pretest-posttest design. Experimental class is a class that is applied to active learnig strategy typeHollywood Squares Review. Data analysis technique used is the t-test. Criteria testing H0 accepted if tcount>ttable  dk = n1 + n2 – 2 with α = 0,05. Based on data analysis of data obtained tcount>ttable is 3,07 >1.67, means  that the use of active learning strategy typeHollywood Squares Review can improve student learning achievement on the subject of Hidrocarbon and Petroleumin class XI MIA SMAN 2Pekanbaru. The category improvement of student achievement at experiment class was high category with N-gain normalized is 0,82.